The Five Cs of Digital Curation: Supporting Twenty-First-Century Teaching and Learning - Mark E. Deschaine, PhD; Sue Ann Sharma, PhD (Park University, 2015)
Digital curation is a process that allows university professors to adopt resources from multidisciplinary fields to meet the educational needs of twenty-first-century learners. Looking through the lens of new media literacy studies (Vasquez, Harste, & Albers, 2010) and new literacies studies (Gee, 2010), we propose that university professors be savvy consumers of multimedia through purposeful content curation. In this paper, we will discuss practices that university professors may use to transform teaching and learning through effective collection, categorization, critiquing, conceptualization, and circulation of resources deemed to have curricular and content standards value.